1999
DOI: 10.1097/00002800-199911000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Pain During Insertion of Peripheral Intravenous Catheters With and Without Intradermal Lidocaine

Abstract: Phase 1 of this study evaluated the perception of pain in 50 patients undergoing peripheral venous catheter insertion without the use of a local anesthetic. Phase 2 evaluated perceived pain in 50 patients who received intradermal lidocaine before the i.v. catheter was inserted. The researchers found that lidocaine injected intradermally before placement of an i.v. catheter resulted in significantly lower self-reported pain perceptions (p < 0.01). No additional time (determined in intervals of 15 minutes) was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Update searches (September 2014 and August 2015) identified six additional studies, giving a total of 37 primary research studies. Thirty two were randomised controlled trials [ 1 , 13 17 , 27 52 ], four were controlled trials [ 53 56 ]} and one was a survey [ 57 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Update searches (September 2014 and August 2015) identified six additional studies, giving a total of 37 primary research studies. Thirty two were randomised controlled trials [ 1 , 13 17 , 27 52 ], four were controlled trials [ 53 56 ]} and one was a survey [ 57 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcome, pain, was measured in a variety of ways including: a visual analogue scale (VAS) ( n = 22 studies [ 1 , 14 – 17 , 27 , 30 32 , 35 , 37 , 39 – 41 , 43 , 44 , 46 49 , 51 53 , 56 ]), a numerical rating scale ( n = 6, [ 13 , 29 , 34 , 38 , 50 , 54 ]), Wong Baker Faces ( n = 1, [ 28 ]) and, other ( n = 4 [ 30 , 33 , 36 , 45 ]). Four studies reported that participants had been given pre-medication prior to PVC [ 29 , 42 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…This percentage is within the range of previously reported failure rates of from 9% to 56%. [3][4][5]8,9 Unsuccessful IV insertion attempts can adversely affect patients' attitudes about the nurse and perceptions about the nurse's caring. Patients' perceptions of nurse caring are strongly linked to their beliefs about the nurse's skill in technical procedures such as IV insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have published cannulation success rates have found this figure in control groups to range from 71-100%. 3,5,7,10 The success rate in the control arm of this study is at the lower end of this range. There are several reasons for this.…”
Section: Discussionmentioning
confidence: 79%